Characterization of the cold-adapted -alpha-tubulin from the psychrophilic ciliate Euplotes focardii - PUCCIARELLI, Sandra; MICELI, Cristina (Extremophiles, 2002)
Tubulin dimers of psychrophilic organisms can polymerize into microtubules at temperatures below 4 degrees C, at which non-cold-adapted microtubules disassemble. This capacity requires specificities in the structure and/or in the posttranslational modifications of the tubulin subunits. A contribution to the knowledge of these specificities was provided by the finding that the amino acid sequence of the alpha-tubulin of the Antarctic ciliate Euplotes focardii contains substitutions that, in addition to conferring an increased hydrophobicity to the molecule, modify sites that are involved in alpha-/alpha-tubulin lateral contacts between protofilaments. At the level of the coding sequence, the alpha-tubulin gene of E. focardii revealed an A+T content appreciably higher than in its homologs in ciliates of temperate waters. This was interpreted as an adaptation to favor DNA strand separation in an environment which is energetically adverse.